Interdialytic weight gain and pre-dialysis mean arterial pressure on patients with chronic hemodialysis - Wahyu Hidayati; Elingga Widi Pangestu; Lestariningsih Lestariningsih; Tri Nur Kristina (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Patients with chronic kidney disease on hemodialysis (CKD-HD) frequently experience an increase in fluid volume, which is largely shown by interdialytic weight gain (IDWG). An increase in IDWG may cause the mean arterial pressure (MAP) during dialysis to increase. Chronic renal disease patients, it might worsen their condition and implies a change in intravascular. Patients must control their fluid intake, nevertheless, there are still a lot of patients who struggle with this. The aim of this study was to investigate the relationship between IDWG and pre-dialysis MAP in patients with chronic kidney disease. A descriptive correlation method with a cross-sectional approach was used in this study. The instruments were observation sheets to note the weight dan blood pressure, weight scales, and a sphygmomanometer. The purposive sampling method was used to select the respondents in this study. The respondents were 52 CKD-HD patients over the age of 18 who exercise at least twice a week and are not in intensive care. The data was collected at a hemodialysis unit. Statistical analysis used Pearson’s product-moment correlation. The results showed that most of the respondents had IDWG in the adequate category (78.8%) and pre-dialysis MAP in the optimal category (23.1%), p=0.003 (less than 0.05) and r=0,41. This study concluded that there was a relationship with moderate strength between IDWG and pre-dialysis MAP in patients with chronic kidney disease. Nurses are urged to strengthen monitoring of IDWG and pre-dialysis MAP, as well as monitoring of dietary compliance and patient fluid intake limitations, to identify potential issues in patients with chronic renal disease.